Musical Bridges to Memory: A Pilot Dyadic Music Intervention to Improve Social Engagement in Dementia. (25th October 2022) - Schafer, Rhiana; Karstens, Aimee; Hospelhorn, Emma; Wolfe, Jeffrey; Ziemba, Amanda; Wise, Peggy; Crown, Rickie; Rook, Jenni; Bonakdarpour, Borna
Abstract : Background: Music-based psychosocial interventions may provide effective management of behavioral symptoms in persons with dementia (PWDs). However, there has been a paucity of studies that measured their effect on social engagement. This proof-of-concept study evaluates efficacy of the Musical Bridges to Memory (MBM) intervention on PWD's social engagement, behavioral symptoms, and associated caregiver distress. Methods: Twenty-nine PWDs and caregivers (8 control dyads, 21 intervention) participated in this dyadically designed, prospective, blinded, 12-week controlled interventional study. The intervention consisted of weekly MBM sessions, led by board-certified music therapists and performers, including caregiver training, live performances, and social breakout groups. Outcomes were measured by the Verbal and Nonverbal Interaction Scale for Care Receivers (VNVIS-CR) to code interactions between PWDs and caregivers for verbal and nonverbal sociable and unsociable behaviors. Symptom severity and caregiver distress were measured using Neuropsychiatric Inventory. Results: Nonverbal sociable interactions significantly increased ( P =0.012) in those who completed the MBM program as compared with a decrease observed in the control group. Family/caregiver distress associated with PWDs neuropsychiatric symptoms showed significant improvement in the experimental group as compared with controls ( P =0.045). Conclusions: This study provides proof-of-concept that MBM improves nonverbal sociable content of PWDs interactions and reduces caregivers' distress.